2017
DOI: 10.1073/pnas.1714019114
|View full text |Cite
|
Sign up to set email alerts
|

STAT5-mediated chromatin interactions in superenhancers activate IL-2 highly inducible genes: Functional dissection of the Il2ra gene locus

Abstract: Cytokines critically control immune responses, but how regulatory programs are altered to allow T cells to differentially respond to distinct cytokine stimuli remains poorly understood. Here, we have globally analyzed enhancer elements bound by IL-2-activated STAT5 and IL-21-activated STAT3 in T cells and identified as the top-ranked gene regulated by an IL-2-activated STAT5-bound superenhancer and one of the top genes regulated by STAT3-bound superenhancers. Moreover, we found that STAT5 binding was rapidly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 40 publications
16
63
0
Order By: Relevance
“…Transcriptomic analyses of STAT5ca-expressing CD8 T cells highlighted a role for STAT5ca in the stabilization of a broad Tc-1 gene expression program initiated by TCR stimulation [60] (see Table 2, Figure 2). This observation is in agreement with the reported chromatin interactions of STAT5 in super-enhancers to activate IL-2 highly inducible genes [71]. .…”
Section: Role Of Stat5 In the Generation Of Memory Cd8 T Cells And Masupporting
confidence: 93%
See 1 more Smart Citation
“…Transcriptomic analyses of STAT5ca-expressing CD8 T cells highlighted a role for STAT5ca in the stabilization of a broad Tc-1 gene expression program initiated by TCR stimulation [60] (see Table 2, Figure 2). This observation is in agreement with the reported chromatin interactions of STAT5 in super-enhancers to activate IL-2 highly inducible genes [71]. .…”
Section: Role Of Stat5 In the Generation Of Memory Cd8 T Cells And Masupporting
confidence: 93%
“…Intriguingly, IL-21 was shown to promote in vitro proliferation of CD8 T naïve and memory cells in synergy with STAT5-inducing cytokines IL-7/IL-15 [90]. Indeed, Leonard's group reported that IL-2 vs. IL-21 cytokine stimulation of pre-activated T cells induces STAT5 and STAT3 binding, respectively, to incompletely overlapping super enhancers [71]. Understanding the fine-tuning of cytokine-modulated STAT3/5 activities will require further effort as reviewed in [46]: This tight regulation relies on the T cell context, including cell lineage, differentiation state, and cytokine milieu, triggering synergistic/antagonistic STAT-mediated transcriptional regulation.…”
Section: Role Of Stat3 In T Cellsmentioning
confidence: 99%
“…STAT5 is not only central to hematopoietic lineages and mammary luminal cells that depend on cytokines ( 44 , 45 ), but also modulates gene expression in other cell types. The precise and cell-specific roles of STAT5-based enhancers might depend on context, possibly their relative position within super-enhancers, relative distance to promoters or accessibility in permissive chromatin ( 10 , 39 , 46 , 47 ). Chromatin accessibility is considered as a key to transcription factor binding and activating gene expression ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…This differential STAT activation leads to differential gene expression by these cytokines. It is established that STAT proteins are critical components of cytokine-activated enhancers, but recently their roles related to super-enhancers ( 70 ) and their abilities to fine-tune gene expression ( 71 ) have been elucidated, with, for example, greater IL-2-inducibility of genes with STAT5-based super-enhancers, as compared to STAT5-based typical enhancers ( 71 ). As opposed to typical enhancers, where factor binding occurs in more limited regions, super-enhancers (also known as stretched or clustered enhancers) ( 70 , 72 , 73 ) represent groups of putative enhancers in close genomic proximity that span broader regions (Figure 2 ), are densely bound by transcriptional coactivators, and usually are associated with high levels of the active chromatin mark histone H3 lysine 27 acetylation (H3K27Ac).…”
Section: T Cell Responses To Different Stimuli Including Il-2 and Il-mentioning
confidence: 99%